Health-related problems of UPV-CM students - Arellano, Ann Mae
Health related problems often serve as an impediment for University students in their learning in the University. It is often stressful for most that lives far from their home. They have to spend extra for the medical bills. This study focused on citing the most rampant diseases, which strikes the students. Through this study, the students would be informed of these diseases so they could prevent it beforehand. And also, make them aware of the services the UPV Health Unit provides. Random sampling method is used to identify the respondents in the study. They are all UPV College of Management students from each year level (1st year-4th year). We took 20 samples from each year level, 10 male and 10 female. The result from the data gathering and analysis proved that most students are not really particular with regards to their health.